2017
DOI: 10.1084/jem.20170399
|View full text |Cite
|
Sign up to set email alerts
|

Cilia loss sensitizes cells to transformation by activating the mevalonate pathway

Abstract: Cilia loss is common in cancer, and its roles remain unknown. Deng et al. show that cilia loss sensitizes cells to transformation by activating a mevalonate pathway through β-catenin–TCF signaling. The mevalonate pathway inhibitor statin blocks the progression of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 42 publications
4
46
0
Order By: Relevance
“…Seeley el al investigated oncogenic Kras‐driven mouse models for pancreatic cancer displaying a down‐regulation of PC during the transition from normal pancreas tissue to precursor lesions. Tissue‐specific knockdown of PC in this mouse model was found in another study to promote tumor formation by activating the mevalonate pathway . The work of Seeley et al also described the absence of PC in precursor lesions of patients and concluded that the down‐regulation of PC is an early event in pancreatic carcinogenesis.…”
Section: Pc In Epithelial Cancersmentioning
confidence: 56%
“…Seeley el al investigated oncogenic Kras‐driven mouse models for pancreatic cancer displaying a down‐regulation of PC during the transition from normal pancreas tissue to precursor lesions. Tissue‐specific knockdown of PC in this mouse model was found in another study to promote tumor formation by activating the mevalonate pathway . The work of Seeley et al also described the absence of PC in precursor lesions of patients and concluded that the down‐regulation of PC is an early event in pancreatic carcinogenesis.…”
Section: Pc In Epithelial Cancersmentioning
confidence: 56%
“…These genes were cloned into the p23/pLKO.1 vectors or for transient (using the Lipofectamine 2000 according to the manufacturer's instructions; Thermo Fisher Scientific, Waltham, MA, USA) or stable expression in 7404 or Huh‐7 cells. The lentivirus was used to produce the stable transformants.…”
Section: Methodsmentioning
confidence: 99%
“…and Gli1 (NM_005269.3) were amplified from reverse-transcribed cDNA from HEK293T cells (KLF2: forward, 5′-ATGGCGCTGAG TGAACCCATCC-3′; reverse, 5′-CTACATGTGCCGTTTCATGT-3′; HDA C1: forward, 5′-ATGGCGCAGACGCAGGGCACCCG-3′; reverse, 5′-TC AGGCCAACTTGACCTCCT-3′; and Gli1: forward, 5′-ATGTTCA ACTCGATGACCCC-3′; reverse, 5′-TTAGGCACTAGAGTTGAGGAA-3′) and then were cloned into P23, pcDNA3.1 and pCMV-HA vectors, respectively, to obtain the Flag, myc and HA tag. Plasmids were sequenced at Sangon Biotech (Shanghai, China) to confirm the sequence accuracy.These genes were cloned into the p2329 /pLKO.1 30 vectors or for transient (using the Lipofectamine 2000 according to the manufacturer's instructions; Thermo Fisher Scientific, Waltham, MA, USA) or stable expression in 7404 or Huh-7 cells. The lentivirus was used to produce the stable transformants.…”
mentioning
confidence: 99%
“…Unlike the motile cilia, the primary cilia are microtubule‐based organelles located at the cytomembrane that act as sensors to receive physical and chemical signals . In the past ten years, this largely ignored organelle has been brought to the forefront of cancer research . Loss of cilia was observed in various cancer cells and gradually regarded as a common hallmark of the disease .…”
Section: Introductionmentioning
confidence: 99%
“…9 In the past ten years, this largely ignored organelle has been brought to the forefront of cancer research. [9][10][11][12] Loss of cilia was observed in various cancer cells and gradually regarded as a common hallmark of the disease. 9,[11][12][13] Restoring the expression of primary cilia appears to be a promising therapeutic method for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%